MORPHOMETRIC AND GROWTH PATTERNS OF THE BLOOD CLAM (Anadara granosa) FROM THE BAGAN SIAPI-API COASTAL AREA ROKAN HILIR - Silfia Eka Dewi; Eddiwan Eddiwan; Efawani Efawani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This study was conducted in the intertidal zone in the waters of Bagan Siapi-api Rokan Hilir Regency in May-June 2018. This study aims to examine morphometrics and growth patterns in blood clams (Anadara granosa) in Bagan Siapi-api waters. A total of 100 samples (23.89-50.52 mm shell length and 3.85-18.16 grams total weight) were analyzed. From the results of observations it was found that the number of male and female ribs was 8-20, and there were 3 differences in morphometric characteristics between male and female, namely male blood clams longer than females, while female blood shells were wider and thicker than males. Furthermore, the growth pattern of A. granosa was negative allometric, with male b values 1.46 and females 0.74.